A single‐center audit of the indications and clinical impact of prolonged ambulatory small intestinal manometry. Issue 9 (1st May 2018) - Ang, D.; Pannemans, J.; Vanuytsel, T.; Tack, J.
Abstract: Background: Small bowel manometry is a diagnostic test available only in a few specialized referral centers. Its exact place in the management of refractory symptoms is controversial. Methods: The records of all patients who underwent 24‐hour ambulatory duodenojejunal manometry over a 6‐year period were retrospectively reviewed. We studied the clinical indications for small bowel manometry, and reviewed the impact of manometric findings on the clinical outcome. One hundred and forty‐six studies were performed in 137 patients (46M, 91F) with a mean age of 44.9 ± 15.7 years. Mean follow‐up duration was 15.1 ± 22.6 months. Appropriate endoscopic, radiological and gastric scintigraphy studies were performed in all patients prior to small bowel manometry. Criteria for abnormal motor activity were based on Bharucha's classification. Key Results: The indications for small bowel manometry were chronic abdominal pain (n = 43), slow‐transit constipation (n = 17), refractory gastroparesis (n = 16), chronic diarrhea (n = 7), recurrent episodes of subocclusion (n = 16), postsurgical evaluation (n = 36), suspicion of gut involvement in systemic disease (n = 9), and unexplained nausea (n = 2). The most common finding was a normal 24‐hour ambulatory small bowel manometry (n = 113). Thirty‐three studies yielded abnormal findings which included extrinsic neuropathy (n = 6), intrinsic neuropathy (n = 18), intestinal myopathy (n = 2), and subocclusion (n = 7). Ambulatory small bowel manometry excluded a generalized motility disorder in 77% and had a significant impact on the subsequent clinical course in 23%. Conclusions & Inferences: Ambulatory small bowel manometry is a useful and safe diagnostic tool to complement traditional investigative modalities in patients with severe unexplained abdominal symptoms. Abstract : We report an important role of ambulatory small bowel manometry in carefully selected patients, based on our experience at a single center over a 6‐year period. The confident exclusion of a generalized gastrointestinal motility disorder in patients, with prior extensive evaluation and negative findings, occurred in 75% of our study population.